Fe ultra-small particles anchored on carbon aerogels to enhance the oxygen reduction reaction in Zn-air batteries. Issue 11 (19th February 2021) - Shi, Jinjin; Shu, Xinxin; Xiang, Chensheng; Li, Hong; Li, Yang; Du, Wei; An, Pengfei; Tian, He; Zhang, Jintao; Xia, Haibing
Abstract : The Fe–N4 –O–Fe–N4 moiety as active sites in ultra-small Fe particles anchored on carbon aerogel exhibited superior performance towards the oxygen reduction reaction. Abstract : In this work, ultra-small Fe particles (Fe-UPs) anchored on carbon aerogel (CA) (Fe-UP/CA catalysts) are successfully prepared by the optimal pyrolysis of hollow composite particles of zeolitic imidazolate framework-8 (ZIF) coated with coordination complexes of tannic acid (TA) and Fe precursors. Within these Fe-UPs, each Fe–N4 moiety is separated by one O atom while each Fe atom is coordinated with four N atoms and one O atom. The as-prepared Fe-UPs composed of the Fe–N4 –O–Fe–N4 moiety (FeFe–O–Fe -UPs) are proposed as a new type of active species for the first time, to the best of our knowledge. Moreover, different types of active species (such as Fe single atoms, FeFe–O–Fe -UPs, and Fe nanoparticles) in the CA can be controlled by rationally adjusting the Fe-to-TA molar ratios. More importantly, FeFe–O–Fe -UPs in Fe-UP/CA catalysts are realized at an Fe-to-TA molar ratio of 2.2. With the merits of both Fe-single atom and traditional Fe-NPs, the as-prepared FeFe–O–Fe -UP/CA catalysts are able to regulate properly the adsorption of reactants and the desorption of intermediates and products due to their increasing size and the presence of the multi-metal-atom structure. Accordingly, the as-prepared FeFe–O–Fe -UP/CA catalysts towards the oxygen reduction reaction (ORR) exhibit a higher half-wave potential (0.93 V vs. 0.89 V of Pt/C), a higher onset potential (1.08 V vs. 1.0 V of Pt/C), a higher kinetic current density (14.2 mA cm −2 at 0.9 V) and better long-term stability in alkaline media. Additionally, Zn-air batteries assembled with such electrocatalysts also exhibit a higher power density of 140.1 mW cm −2 and a larger specific capacity of 781.7 mA h g −1, which are better than those of the state-of-the-art the commercial Pt/C catalyst.